Induksi Kalus Tanaman Puspa (Schima wallichii (DC.) Korth) dengan Penambahan Beberapa Konsentrasi Benzyl Amino Purin (BAP) dan 2,4-Diklorofenoksiasetat (2,4-D) - Husri Meli; Zozy Aneloi Noli; Suwirmen Suwirmen (Universitas Andalas, 2019)
The research about Callus Induction of Puspa (Schima wallichii (DC.) Korth) with several concentrations addition of Benzyl Amino Purine (BAP) and 2,4-Dichlorophenoxyacetid acid (2,4-D) had been done from October until November 2016 at Plant Physiology dan Tissue Culture Laboratory, Biology Department, Faculty of Mathematics and Natural Science, Andalas University. The aim of this researh is to get the combination of 2,4-D and BAP to induce the best callus of Schima wallichii. This research used a Completely Randomized Design Method with 10 treatments and 3 replications. The result showed that combination of 2 ppm 2,4-D + 0,75 ppm BAP was the best concentration to induce callus of Schima wallichii.